VD_FINDINFO AP / 2011 / 30 vom 11. November 2010 - VD Tribunal cantonal (2010)
PEINE ACCESSOIRE, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, SEMI-DÉTENTION | 183 ch. 1 CP, 42 al. 4 CP, 47 CP, 157 CPP, 370 CPP, 19 ch. 2 LStup